1963
DOI: 10.1149/1.2425840
|View full text |Cite
|
Sign up to set email alerts
|

The Corrosion of 1100 Aluminum in Oxygen-Saturated Water at 70°C

Abstract: In oxygen‐saturated distilled water at 70°, the rate and amount of corrosion during short exposure are influenced by experimental conditions. One noteworthy effect is that contamination of the water by the reaction increases the corrosion rate. Subsequent to the first several days, the amount of corrosion varies with the logarithm of the exposure time. This behavior holds for at least 180 days; it is believed to hold for as long as tests have provided reasonable data, the longest being about 650 days. These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1965
1965
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In our own research on the corrosion of 1100 aluminum, it has been observed that at 70~ and below, a heavy layer of porous, not significantly protective, bayerite covers a thinner layer (4,5). This protective layer is believed to be boehmite on the basis of our own (4) and other observations of early formation (6)(7)(8).…”
mentioning
confidence: 79%
“…In our own research on the corrosion of 1100 aluminum, it has been observed that at 70~ and below, a heavy layer of porous, not significantly protective, bayerite covers a thinner layer (4,5). This protective layer is believed to be boehmite on the basis of our own (4) and other observations of early formation (6)(7)(8).…”
mentioning
confidence: 79%
“…Draley et al measured the corrosion of 1100 aluminum in oxygen-saturated waster at 70 °C at a 6.5 pH for up to 1.5 years, using two corrosion vessels. [2] Each vessel tested contained multiple samples. The water in the first vessel was refreshed with fresh water while the second received water from the first vessel (carrying corrosion products from the corrosion in the first vessel).…”
Section: Literature Modelsmentioning
confidence: 99%
“…The actual oxide film might be porous, which would tend to increase the thickness for a given mass of oxide. [2], the authors refer to some of their previous findings of aqueous corrosion of 1100, stating that "After sufficiently extended exposure, bits of the corrosion product slough or flake off, leaving a metallic sheen. The corrosion product does not again grow thick in those places, and there is no observable increase in corrosion of the specimens.…”
Section: Literature Modelsmentioning
confidence: 99%
“…[96] This corrosion product is a multi-layered aluminum oxide and there is evidence that dissolution of at least one of these layers can have a significant effect on the corrosion rate. [97][98][99][100][101] The dissolution rate is a function of at least three different variables (temperature, pH, and refreshment rate), but there is no generally accepted model of the detailed behavior. Also, care should be taken during storage in air to keep humidity or contamination (e.g., from fingerprints) from plate surfaces, particularly if the plates have not been cleaned and passivated.…”
Section: Corrosion Behaviormentioning
confidence: 99%